Correction: Implementing a structured model for osteoarthritis care in primary healthcare: A stepped-wedge cluster-randomised trial. - Nina Østerås; Tuva Moseng; Leti van Bodegom-Vos; Krysia Dziedzic; Ibrahim Mdala; Bård Natvig; Jan Harald Røtterud; Unni-Berit Schjervheim; Thea Vliet Vlieland; Øyvor Andreassen; Jorun Nystuen Hansen; Kåre Birger Hagen (PLoS Medicine)
[This corrects the article DOI: 10.1371/journal.pmed.1002949.].